Kepemilikan Manajerial dan Kepemilikan Institusional terhadap Related Parties Transactions Dengan Kepemilikan Minoritas Sebagai Pemoderasi Studi Pada Industri Tambang Sektor Batubara terdaftar di Bursa Efek Indonesia Periode 2015-2021 - Agustine Sulviani (Departement of Mathematics Education, 2023)
This study aims to analyze Managerial Ownership and Institutional Ownership of Related Parties Transactions with Minority Ownership as Moderators. The object of this research was the Coal Sector Mining Industry listed on the Indonesia Stock Exchange for the 2015-2021 period. The population in the study amounted to 23 companies with the sampling method using purposive sampling. The sample numbered 6 sample companies with sample data totaling 42 pooled observation data. The analysis used is multiple regression analysis to test data and hypothesis statements. The results of this study are that minority ownership is able to moderate institutional ownership of RPT so that coal mining companies listed on the IDX are able to maintain RPT efficiency through effective supervision by institutional ownership. Minority ownership is also able to moderate institutional and managerial ownership, RPT efficiency can be maintained through effective supervision by the collaboration of institutional and managerial ownership.